Intestigation of the effect of a mixture of sprouted grains on the quality and nutritional value of bakery products - Burchenko, Liudmyla; Bilyk, Olena; Bondarenko, Yulia; Perederii, Inna; Kochubei-Lytvynenko, Oksana (Technology audit and production reserves, 2018)
The object of research in the work is wheat bread, enriched with a mixture of sprouted grains. In sprouted grains due to the technology of soaking, the process of sprouting and drying, natural properties are preserved and multiplied. The protein contained in the sprouted grain of wheat, oats, barley and maize contains all the essential amino acids, which in percentage are up to 30 % of the total protein content. 5...10 times more vitamins of group B, H, E, PP and others. All high molecular weight compounds with high nutritional value are split into sprouted grains and are easily digested. A possible lack of use of sprouted grain in bread technology is high autolytic activity and acidity. This must be considered when improving the process. During the research, a mixture of sprouted grains of the Ukrainian producer LLC «Choice» (Kyiv) was used, which has the appearance of a powder that has a slightly sweet taste. It is established that the use of a mixture of sprouted grains in the technology of wheat bread activates the fermentation activity of the dough microflora, promotes the use of accelerated technology. The introduction of a mixture of sprouted grains increases the shelf life of fresh products. The obtained results are related to the improvement of the nutrition of the yeast microflora of the dough due to the content of sugars introduced with a mixture of sprouted grains. Intense coloring of the products crust is a consequence of the fact that the products of starch hydrolysis more actively react to melanoid formation. The slowing down of the staling of products with a mixture of sprouted grains, apparently, is due to the slowing down in them of the retrogradation of starch and the accumulation of low molecular weight dextrins due to active α-amylase. Due to the dosing of the mixture of sprouted grains in the amount of 5, 10 and 15 % by weight of the flour, the energy value of wheat bread increases in accordance with 252.7, 262.9 and 273.1 kcal, compared with the control – 232.3 kcal. The introduction of bread with a mixture of sprouted grains in the production will contribute to the expansion of the range of bakery products gerodietary destination.